2014
DOI: 10.1039/c4cc02991g
|View full text |Cite
|
Sign up to set email alerts
|

A novel mechanism for poisoning of metal oxide SCR catalysts: base–acid explanation correlated with redox properties

Abstract: A novel mechanism is proposed for the poisoning effect of acid gases and N2O formation on SCR catalysts involving base-acid properties correlated with redox ability of M-O or M-OH (M = Ce or V) of metal oxides and the strength of their basicity responsible for resistance to HCl and SO2 at medium and low temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 30 publications
0
36
0
Order By: Relevance
“…[ 36 ] The peaks at 1770 and 1625 cm −1 could be attributed to the formation of bidentate and carbonate, respectively, and signified a nucleophilic attachment to O 2− clusters. [ 37 ] Unlike Ga 15/ ZSM‐5, however, all peaks disappeared on V 15 /ZSM‐5 by the tenth minute of desorption at 200 °C (Figure 2d). This signified that carbonyl and bidentate bonding to the vanadium oxide centers was weaker than the carbonate bonding in Ga 15 /ZSM‐5 and indicated that V 15 /ZSM‐5 was less basic than Ga 15 /ZSM‐5.…”
Section: Resultsmentioning
confidence: 99%
“…[ 36 ] The peaks at 1770 and 1625 cm −1 could be attributed to the formation of bidentate and carbonate, respectively, and signified a nucleophilic attachment to O 2− clusters. [ 37 ] Unlike Ga 15/ ZSM‐5, however, all peaks disappeared on V 15 /ZSM‐5 by the tenth minute of desorption at 200 °C (Figure 2d). This signified that carbonyl and bidentate bonding to the vanadium oxide centers was weaker than the carbonate bonding in Ga 15 /ZSM‐5 and indicated that V 15 /ZSM‐5 was less basic than Ga 15 /ZSM‐5.…”
Section: Resultsmentioning
confidence: 99%
“…The first desorption peak centered at around 120 • C corresponds to the physisorbed NH 3 or weakly acidic sites [34]. The other peak located at around 480 • C can be assigned to the chemical adsorbed ammonia on strong Lewis and Brønsted acidity sites [35]. The amount of total NH 3 adsorption and the proportion for every type of acid site were calculated from the integrated areas of the corresponding peaks.…”
Section: -mentioning
confidence: 99%
“…The selective catalytic reduction of NOx by NH3 (NH3-SCR) is one of the most popular methods for the removal of NOx from stationary sources. Though V2O5-WO3/TiO2 displays excellent activity in NH3-SCR and is the predominantly the main commercial catalyst for this process, many compounds containing alkali/alkali earth metal elements, Pb, Zn, As or Cl are commonly found in flue gas streams, can lead to the de-activation of V2O5-WO3/TiO2 catalysts [1][2][3][4]. In addition to the pre-viously mentioned composite species, SO2 is also a common component of many industrial flue gas streams where the combustion of sulfur-containing fuels occurs.…”
Section: Introductionmentioning
confidence: 99%